Autopsy as a Teaching Methodology In Forensic Medicine: Students’ Perspective: Teaching Methodology In Forensic Medicine - Yousaf, Nida; Ali, Shoukat; Anwar, Malik Adeel; Murtaza, Mazhar; Malik, Hamna; Sukhera, Khyzer Hayat; Akram, Roman (Pakistan Journal of Health Sciences, 2025)
Autopsy as a teaching tool has been historically accepted as a valued method for medical students but its usage has been reduced due to newer technologies being available. Objective: To assess the students opinions’ on autopsy as a learning tool and their views on alternative teaching methods. Methods: A cross-sectional questionnaire-based study was conducted in 2024 at Rashid Latif Medical College. Prevalidated questionnaires were distributed among the third year MBBS students and participation was voluntary. 115 complete questionnaires were analyzed by SPSS version 25.0. Results: All participants demonstrated an understanding of autopsy and considered its significance in medical education as a learning tool. 36.52% and 47.83% of the students considered videos and printed materials respectively as viable alternatives. However, 80.87% of students agreed that medical students should observe more autopsies for better understanding and appreciate their role in forensic and clinical correlation. Conclusions: Although students are aware of the potential benefits of autopsy, there is still a need to further emphasize its importance in this modern medical training. Without firsthand exposure, future doctors may struggle to explain procedures that have never been witnessed.